An asymmetric analysis of the impact of foreign and domestic debt on South Africa's economic growth - Gisele Mah (Economies, 2025)
South Africa has been struggling with high levels of gross debt. The COVID-19 pandemic has worsened as the government has had to adjust its budget continuously, resulting in fiscal stance and debt sustainability becoming a matter of concern. This research aims to assess the possible asymmetric effect of foreign and domestic debt on economic growth in South Africa. Annual data from 1960 to 2023 was obtained from the South African Reserve Bank for the following variables: total domestic debt as a percentage, total foreign debt as a percentage, and gross domestic product. The nonlinear autoregressive distributed lag was used, and the results reveal that a positive change in total domestic debt has a negative and significant effect on GDP. A negative change in total domestic debt as a percentage has a positive and significant effect on GDP. These results suggest that South Africa's GDP responds significantly to a decrease in total domestic debt when compared to an increase in total domestic debt. A positive change in total foreign debt as a percentage has a positive and statistically significant effect on GDP. A negative change in total foreign debt as a percentage has a negative and statistically insignificant relationship with GDP. In South Africa, foreign debt has a positive relationship, while domestic debt has a negative relationship with gross domestic product in South Africa. This means that for the gross domestic product to increase, there is a need for an increase in foreign debt and a decrease in total domestic debt in South Africa. The foreign debt should be at a certain level to avoid high debt services.
Keywords: H63; H68; O43; C14; 330; foreign debt; domestic debt; NARDL; GDP gap; South Africa